Prospective Clinical Study of Keratoconus Progression in Patients Awaiting Corneal Cross-linking. Issue 10 (October 2020) - Goh, Yi Wei; Gokul, Akilesh; Yadegarfar, Mohammad E.; Vellara, Hans; Shew, William; Patel, Dipika; McGhee, Charles N. J.; Ziaei, Mohammed
Abstract : Purpose: Keratoconus progression should be treated with corneal cross-linking (CXL) in a timely manner. This study aimed to investigate patient factors associated with keratoconus progression between time of listing and at time of CXL. Methods: Prospective observational study at a tertiary center. Ninety-six eyes of 96 patients with keratoconus. Demographic, clinical, and tomographic parameters were analyzed to determine the risk factors for keratoconus progression. Analyzed tomographic indices included steepest keratometry, average keratometry, cornea thinnest point, index of surface variance, index of vertical asymmetry, keratoconus index, center keratoconus index, index of height asymmetry, and index of height decentration. Results: A total of 38 eyes (39.6%) were found to have keratoconus progression during an average waiting time of 153 ± 101 days. There were significant differences in preoperative tomographic parameters such as index of surface variance (111.3 ± 36.6 vs. 88.3 ± 31.8; P = 0.002), index of vertical asymmetry (1.1 ± 0.4 vs. 0.9 ± 0.4; P = 0.005), keratoconus index (1.31 ± 0.12 vs. 1.22 ± 0.11; P < 0.001), and index of height decentration (0.16 ± 0.07 vs. 0.11 ± 0.06; P = 0.015) between eyes that progressed and those that remained stable. There were no significant differences in steepest keratometry, average keratometry, cornea thinnest point, and center keratoconus index. Multivariate analysis did not reveal age, presence of atopy/atopic keratoconjunctivitis, eye rubbing, or waiting time to be a significant risk factor for progression; however, Maori ethnicity was a risk factor (odds ratio = 3.89; P = 0.02). Conclusions: A significant proportion of eyes were found to be progressing while waiting for CXL. A risk stratification score for patients awaiting CXL may reduce the risk of progression.